Mind the gap: A comparison of socio-technical limitations of national house rating systems in the UK and Australia. (November 2021) - Miller, Wendy; Sodagar, Behzad; Whaley, David; Bamdad, Keivan; Zedan, Sherif
Abstract: This paper reviews the national house rating tools in the UK and Australia, evaluates the energy performance of eight different case study houses, and quantifies the magnitude of the performance gap between as-designed energy performance and as-occupied (actual) energy use. To identify contributing factors to the performance gap, post-occupancy evaluations were conducted, and all case study houses were monitored over two years. It was observed that there are performance gaps in all case study houses, however, the gap can be negative (i.e. more actual energy use than simulated) or positive (i.e. less actual energy use than simulated). Results show that the actual heating loads were less than simulated in 5 of the 8 houses (2 UK and 3 AU), and only 1 house (AU) had an actual cooling load more than simulated. The heating discrepancies ranged from 73% to 180% for the UK houses, and 19%–172% for the AU houses. For the cooling loads, actual energy use in the AU house was up to 4.8 times higher than the simulated. To understand the underlying causes, several influencing factors (including internal temperature conditions, climate, house form and urban context, construction quality, and processes and assumptions of national house rating tools) were analysed. It was found that a key challenge relates to a limited definition of the energy system (household energy use), focusing on technical issues and largely ignoring or simplifying existing and changing socio-cultural issues. Additionally, the paper argues for the need for extending the system boundary beyond individual buildings to neighbourhood, community and city scales. At both a building scale and community scale, deeper understandings of socio-cultural issues that impact on, and are impacted by, energy metabolism, are required. Highlights: The national house energy rating systems of the UK and Australia were reviewed. Energy performance of eight case study houses were monitored over two years. Both positive and negative performance gaps were observed. Contributing factors to the performance gap were identified using measurements and POE. More attention to socio-cultural indicators can improve the design of rating tools.